Taxation and Corporate Debt : Are Banks any Different? - Heckemeyer, Jost (IMF Working Papers; Working Paper, 2013)
This paper explores whether corporate tax bias toward debt finance differs between banks and nonbanks, using a large panel of micro data. On average, it finds that there is no significant difference. The marginal tax effect for both banks and non-banks is close to 0.2. However, the responsiveness differs considerably across the size distribution and the conditional leverage distribution. For nonbanks, we find a U-shaped relationship between asset size and tax responsiveness, although this pattern does not hold universally across the conditional leverage distribution. For banks, in contrast, the tax responsiveness declines linearly in asset size. Quantile regressions show further that capitaltight banks are significantly less responsive than are capital-abundant banks; the same pattern holds for the largest non-banks. Still, even the largest banks with high conditional leverage ratios feature a significant, positive tax response.